Chronic Basophilic Leukaemia in a Dog. (January 2019) - Azakami, D.; Saito, A.; Ochiai, K.; Ishiwata, T.; Takahashi, K.; Kaji, N.; Kaji, D.; Kaji, N.; Michishita, M.
Summary: A 13-year-old neutered female mixed-breed dog with a clinical history of emaciation, inappetence and vomiting for 2 months was presented. Blood tests showed marked leucocytosis with increased neutrophil and basophil count, mild thrombocytosis and anaemia. Seven days after the initial visit, the dog died and was submitted for necropsy examination. Grossly, the bone marrow was red in colour and hepatomegaly and splenomegaly with discolouration were observed. A bone marrow smear showed an increased proportion of basophilic lineage cells. Histologically, the bone marrow showed high cellular density and numerous basophilic lineage cells with a round or segmented nucleus. The cytoplasm contained basophilic granules exhibiting metachromasia on toluidine blue staining. Immunohistochemically, the neoplastic basophils were diffusely positive for vimentin and myeloperoxidase, but negative for CD3, BLA36, CD163, CD204 and c-kit. The immunohistochemical features of neoplastic basophils that had invaded the liver and spleen were similar to those of the basophils in the bone marrow. Based on the clinicopathological and histopathological findings, chronic basophilic leukaemia was diagnosed. The present case study provides insights into the pathological features of chronic basophilic leukaemia in dogs.